2019
DOI: 10.1002/col.22433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold plasma on the color parameters of Hyssop (Hyssopus officinalis L.) using color imaging instrumentation and spectrophotometer

Abstract: This research was conducted to evaluate the effects of cold atmospheric plasma treatment on the color of Hyssop (Hyssopus officinalis L.) and also to compare the usage of the spectrophotometer vs the color imaging instrumentation for the evaluation of the treatment on the color parameters. The experiments were investigated at different treatment times of 1, 5, and 10 minutes and the voltage values of 17, 20, and 23 kV. Possible changes of color were evaluated by using CIE L*a*b* values obtained with HunterLab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Additionally, the b* value increased from 24.87% (CP-5) to 56.30% (CP-15) relative to CP-0, while the a* value decreased from 20.32% (CP-5) to 18.13% (CP-10) relative to CP-0. These color observations align with the findings of Rezaei et al 38 and Hemmati et al 39 The TCD is used to identify the difference in color parameters, i.e., L*, a*, and b*. According to Adekunte et al, 40 TCD can be categorized as very distinct (TCD > 3), distinct (1.5 < TCD < 3), and small difference (TCD < 1.5), with treatments exhibiting lower TCD deemed more appealing to consumers.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…Additionally, the b* value increased from 24.87% (CP-5) to 56.30% (CP-15) relative to CP-0, while the a* value decreased from 20.32% (CP-5) to 18.13% (CP-10) relative to CP-0. These color observations align with the findings of Rezaei et al 38 and Hemmati et al 39 The TCD is used to identify the difference in color parameters, i.e., L*, a*, and b*. According to Adekunte et al, 40 TCD can be categorized as very distinct (TCD > 3), distinct (1.5 < TCD < 3), and small difference (TCD < 1.5), with treatments exhibiting lower TCD deemed more appealing to consumers.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…In freshly cut kiwi, chlorophyll reduction was observed due to CP treatments 34 . In hyssop, using CP for 10 min at 23 kV, the treated sample had a higher Δ E value (6.33) among other values 35 . Plasma modifies the superficial characteristics of materials with a chemical reaction 36 .…”
Section: Resultsmentioning
confidence: 99%
“…34 In hyssop, using CP for 10 min at 23 kV, the treated sample had a higher ΔE value (6.33) among other values. 35 Plasma modifies the superficial characteristics of materials with a chemical reaction. 36 Based on the literature review, the mechanisms may be as follows: (i) physical change following the bombardment of electrons and ions and (ii) oxidation of outer surface compounds and cell damage.…”
Section: Color Propertiesmentioning
confidence: 99%
“…The effect of cold plasma on color values can vary depending on many parameters, including the experimental setup, power, and treatment time. It was reported that cold plasma treatment caused changes in the color parameters of dried hyssop leaves with increasing voltage and exposure time (Rezaei et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%